PENINGKATAN PENGETAHUAN WANITA USIA SUBUR, IBU HAMIL TENTANG PERTOLONGAN PERSALINAN OLEH TENAGA KESEHATAN DAN PERSALINAN DI FASILITAS PELAYANAN KESEHATAN DI DESA LATDALAM KEC. TANIMBAR SELATAN - Kasmiati, Kasmiati; Arvicha Fauziah; Sitti Suharni Hermanses; Jakob L Jambormias (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Childbirth assistance by health workers and childbirth in health facilities is still a problem that is difficult to resolve, especially in Indonesia because of the low level of public knowledge regarding the importance of childbirth assistance by health workers and childbirth in health service facilities. The community still gives full trust to shamans to provide birth assistance. The aim of this service is to provide education in the form of counseling and focus group discussions which are attended by couples of childbearing age and pregnant women in Latdalam Village, South Tanimbar District, Tanimbar Islands Regency. This activity is attended by 20 couples of childbearing age and 12 pregnant women person. The activities were carried out using pretests and posttests to determine changes in knowledge about the importance of childbirth by health workers and childbirth in health service facilities. The results of the service activities were that there was an increase in knowledge from less than 22 people (68.75%) before implementation to less than 1 person (3.12%), there was an increase in knowledge of 65.63%. In conclusion, this service activity is one way to change thought patterns and behavior in the community to increase the achievement of delivery targets by health workers and delivery in health service facilities